Initial Evaluation of Antioxidant and Antibacterial Activities of Several Medicinal Plant Extracts Collected in Vietnam - Anh, Le Tuan; Hang, Pham Thi Thanh; Loan, Nguyen Thi Bich; Mai, Le Quynh (VNU Journal of Science: Natural Sciences and Technology, 2021)
The diversity of medicinal plants in Vietnam is a rich source to develop novel health products. In this study, the antioxidant and antimicrobial activities of ethanolic extracts of Pluchea indica , Drynaria fortunei , Stephania glabra , lemongrass ( Cymbopogon citratus ) and lime ( Citrus aurantifolia ) mixture, and ginger ( Zingiber officinale ) and kumquat ( Citrus japonica ) mixture, were evaluated. The extract of ginger and kumquat mixture exhibited the highest free radical scavenging activity (85%), followed by P. indica and S. glabra (60% and 53%, respectively) at the concentration of 0.1 mg/ml. Moreover, the agar well diffusion assay revealed that the extract of S. glabra and the extract of ginger and kumquat mixture were effective in inhibition against Bacillus cereus , Staphylococcus aureus , and Vibrio parahaemolyticus . Especially, the extract of S. glabra at the concentration of 100 mg/ml showed the highest inhibition zone diameter (13±1.73 mm) against B. cereus , which was significantly larger than that of Ceftriaxone (5 mg/ml) and other extracts.